Florence RockinArt - Alba Patrizia Santo (Dialoghi con la società, 2020)
The city of Firenze represents, for the variety of its artistic and architectural heritage, a kind of open-air museum. Works of art and monuments are mainly made of the rocks outcropping in Firenze and in the surrounding areas; indeed, a close link exists between monuments, geographical position of the city and its history. Florence, is characterised by the color of its stone-built cultural heritage, mainly by the warm ochraceous color of the Medieval Pietraforte sandstone and the cerulean grey of the Renaissance Pietra Serena sandstone together with other natural and artificial materials used to complete or cover the stone walls. The web-app Florence RockinArt was created to deepen the knowledge of the stone materials. It is addressed to all those who are interested in discovering the monuments of Florence by carefully observing the stone materials that make up them. The web-app contains short historical notes on the main monuments and detailed geological, mineralogical and petrographic characteristics of the natural and artificial materials of which they are constituted.